2003
DOI: 10.1890/1051-0761(2003)13[1177:eahfif]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Human Factors Influencing Fire Trends in Enso and Non-Enso Years in Tropical Mexico

Abstract: Tropical and subtropical areas present the vast majority of contemporary global fires. Despite the human origin of most of these fires, little is known of how environmental and socioeconomic variables contribute to the spatial patterns of fire incidence and burned areas. The tropical Mexican State of Chiapas represents a good case study to analyze these interactions, due to the availability of official data, and its similarities to other tropical countries, in terms of environmental and socioeconomic character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 47 publications
0
49
0
2
Order By: Relevance
“…That is, based on a long-term meteorological time series, we test whether the SOI has an effect on monsoon-type rainfall, as suggested by some researchers (29,30).…”
mentioning
confidence: 99%
“…That is, based on a long-term meteorological time series, we test whether the SOI has an effect on monsoon-type rainfall, as suggested by some researchers (29,30).…”
mentioning
confidence: 99%
“…Rajão, personal communication). Remote sensing studies tend to determine fire causality via spatial correlations or regressions of hot spot occurrence with secondary data, such as: gross domestic product or human population density (Roman-Cuesta et al 2003); distance to a feature such as a road; a reserve polygon, or its buffer area , Nepstad et al 2006, Adeney et al 2009. Although effective at broad scales, the coarse resolution of secondary data often prevents these studies from moving beyond generalizations Skole 1998, Wilbanks 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The remote sensing community relies on satellite-derived data, acquired via reflectance values of wavelengths of energy from the earth's surface and used to detect and monitor "hot spots" (Stolle et al 2004). They aim to determine the predictors of fire through statistical models and increasingly combine remotely sensed data with secondary socioeconomic or political data (Roman-Cuesta et al 2003, Alencar et al 2004, Nepstad et al 2006, Adeney et al 2009). Ecologists tend to work at smaller scales and have addressed issues such as the effects of fire on tree mortality and species diversity (Slik et al 2002, Barlow andPeres 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Although ignition is an integral component of wildfire factors, it is crucial in terms of wildfire occurrence, because the possibility of wildfire is minimal, no matter how dry the weather conditions and how high the forest flammability without ignition. Humans have a profound affect on fire regimes by being a source of ignitions (Fusco, Abatzoglou, Balch, Finn, & Bradley, 2016), and human activity is responsible for igniting a majority of all fires (Benali et al, 2017;FAO, 2007;Prestemon & Butry, 2005;Román-Cuesta, Gracia, & Retana, 2003). According to statistics, the main causes of wildfires in China are related to human activities, with lightning accounting for only 0.38% of the total (Zhong, Fan, Liu, & Li, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, an improved understanding of wildfire risk should address the patterns of human activity and its relation to fire ignition (Dickson et al, 2006;Narayanaraj & Wimberly, 2012;Prestemon, Pye, Butry, Holmes, & Mercer, 2002). Significant research effort has been undertaken to explore the relationship between wildfire and its causative factors with the goal of building predictive models (Cardille et al, 2001; Chas-Amil, Prestemon, McClean, & Touza, 2015;Maingi & Henry, 2007;Narayanaraj & Wimberly, 2012;Romero-Calcerrada, BarrioParra, Millington, & Novillo, 2010;Román-Cuesta et al, 2003;Salis et al, 2013;Syphard et al, 2007;Watts & Hall, 2016;Ye, Wang, Guo, & Li, 2017), and has concluded that wildfire tends to occur in areas near human infrastructure on the human-wildland interface (Zhang, Lim, & Sharples, 2016), and frequently exhibits nonlinear relationships (Hawbaker et al, 2013). However, previous studies mainly concentrate on overall wildfire risk integrating numerous factors simultaneously, yet the importance of human factors on ignition has not received much attention.…”
Section: Introductionmentioning
confidence: 99%